2018
DOI: 10.1007/s11249-018-1040-z
|View full text |Cite
|
Sign up to set email alerts
|

Shear Thinning and Hydrodynamic Friction of Viscosity Modifier-Containing Oils. Part II: Impact of Shear Thinning on Journal Bearing Friction

Abstract: In a companion paper, the temporary shear thinning behaviour of a series of viscosity-modifier (VM)-containing blends was studied over a wide shear rate and temperature range [Marx et al. in Tribol Lett, https ://doi.org/10.1007/s1124 9-018-1039-5]. It was found that for almost all VMs the resulting data could be collapsed on a single viscosity versus reduced strain rate curve using time-temperature superposition. This made it possible to derive a single equation to describe the viscosityshear rate behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…The ability to derive a single equation (Eq. 12) to describe the shear thinning of a given VM blend is important since it enables quantification of the impact of VM on shear thinning over a wide range of conditions and can also be used in modelling of the hydrodynamic behaviour of VM blends in hydrodynamic lubricated components, as described in the companion paper, Part 2 [1].…”
Section: Alternative Shear Thinning Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to derive a single equation (Eq. 12) to describe the shear thinning of a given VM blend is important since it enables quantification of the impact of VM on shear thinning over a wide range of conditions and can also be used in modelling of the hydrodynamic behaviour of VM blends in hydrodynamic lubricated components, as described in the companion paper, Part 2 [1].…”
Section: Alternative Shear Thinning Equationsmentioning
confidence: 99%
“…In a companion paper, the master shear thinning curves obtained in this paper are used to explore how VMs impact film thickness and friction in a steadily loaded, isothermal journal bearing [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current work, a subset of these oils is studied, as listed in Table 1. The original oil codes used in [1,2] have been retained. Oils #1, #4, #5, #7, and #10 are simple solutions of different VMs in the same 6 cSt KinVis Group II base oil.…”
Section: Test Oils and Viscometricsmentioning
confidence: 99%
“…It was found that for all but one of the VMs, the viscosity of a given blend at all shear rates and temperatures could be described by a single equation based on time-temperature superposition. The resulting shear thinning equations were then used to explore the impact of the VMs on plain bearing friction using an isothermal, 3D hydrodynamic lubrication model [2]. This showed that VMs can reduce friction in two ways, by increasing viscosity index, leading to a low viscosity at low temperatures, and via shear thinning which reduces effective viscosity in high sliding speed, high shear rate lubricated contact conditions [2].…”
Section: Introductionmentioning
confidence: 99%